‘Grounding' ecosystem-based adaptation in the Western Cape Province - Maarstoel, Marte Nogva (Department of Environmental and Geographical Science, 2021)
Ecosystem-based adaptation (EbA) advocates that well-functioning ecosystems are critical for building resilience and supporting society's adaptation to the adverse impacts of climate change. The National Department of Environmental Affairs, Fisheries and Forestry in South Africa has decided to mainstream EbA into its climate response actions, developing a strategy and set of guidelines to steer implementation. However, little work has been done to grasp different actors' perspectives and understandings of EbA, its implementation and how to link EbA to existing related projects and programmes that focus on natural resource management and ecological restoration. This research presents findings from a qualitative study in the Western Cape that sought to investigate what EbA means ‘on the ground' and how it can be actioned. The objectives for this research were to 1) unpack how government actors in the Western Cape relate to, understand and give meaning to EbA in their specific and existing work contexts and how they relate EbA to other concepts such as green infrastructure, restoration and various forms of natural resource management (NRM); 2) explore the concerns and challenges encountered and what support is needed to implement EbA within each actor's sector; and 3) interpret what the findings mean for future conceptualization, and promotion of EbA mainstreaming in the Western Cape. Semi-structured interviews with 19 government officials and participant observation at EbA related events in South Africa were the main methods used in the research. Findings suggest that despite some conceptual confusion related to EbA, EbA can be ‘grounded based on the three spheres EbA explicitly builds on; namely biodiversity and ecosystem conservation, climate change adaptation and socio-economic benefits. That said, the study also found that practitioners might struggle to successfully address climate change as one of the critical areas of EbA, due to the difficulties of integrating climate change science and projections into projects. In addition, three challenges were identified that relate to funding availability, silo mentality and the mismatch between short-term objectives and decision making in government, and the need for long-term thinking and planning. Increased climate change understanding together with effective demonstration and the use of applicable language that relates to what the different actors are already doing can help improve EbA uptake and mainstreaming, as well as address the challenges related to conceptual confusion, funding, silo mentality and short-term thinking.